Manajemen Lembaga Zakat di mata Muzakki - Multifiah - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The aim of this research is to analyze muzakki perception towards management of Zakah Managing Institution (ZMI). Primary data is obtained from common muzakkies and those distributing their zakah by means of the ZMI, the YDSF and the BMH. Analysis is conducted by using qualitative method. Reasearch results reveal that there are three kinds of muzakkies in relation with their assessment of ZMI management. They are (1) muzakkies assessing that ZMI management is good, sincere and professional so that muzakkies distribute their zakah by means of ZMI, and this is the same with what was conducted by Rasullullah SAW, the Prophet; (2) muzakkies trusting and assessing that ZMI management is professional and transparent enough, but distribute a share of their zakah by means of ZMI and for some reasons distribute the other share to mustahiks directly; and (3) muzakkies assessing ZMI management is neither transparent nor professional so that they do not trust the ZMI management, and prefer to distribute their zakah directly to the mustahik.Keywords: Zakah, Zakah managing institution (ZMI) , muzakki, mustahik